La Consultation . The Consultation - Crécy, Hélène de (Mio, Arturo, 2006)
Verzio FF submission The daily routines of a general practitioner, in stark contrast with the highly specialized world of today’s medical practices. Doctor Luc Perino is a hero in his own unspectacular way. He receives people at all stages of life: from newborn babies to the dying, and everyone else who knocks at his door with their complaints: a young man of North-African descent who feels nervous and can't get a job; a young Asian woman with an unwanted pregnancy; a woman with anxiety attacks and an uncommunicative unemployed husband; an older woman whose main problem seems to be that she does not feel at home among the other elderly people in her service flat, and a host of other patients. There are as many people as there are pathologies, as many stories as there are pains, as many situations as there are issues. Doctor Perino does what he can, but during many a conversation you sense a certain despair, which is confirmed by a number of direct comments to the camera after consultations. What can a doctor do in a world with high work pressure, unemployment, bad marriages and fragile old people? Doctor Luc Perino may not be perfect, but he is the best guide we can wish for in the territory of humanity in medicine.